HUBUNGAN SELF-COMPASSION DENGAN SELF-CARE PADA PASIEN DM TIPE 2 YANG MENGALAMI KAKI DIABETIK - I Dewa Putu Gede Putra Yasa; Diana Paramitha Dewi; I Wayan Surasta (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2026)
Introduction: Diabetes mellitus (DM) is a chronic disease resulting from the pancreas's inability to produce insulin optimally. Diabetic foot complications can affect self-compassion and worsen self-care. Methods: This study utilized a descriptive correlational design with a cross-sectional approach. The purpose of this study was to determine the relationship between self-compassion and self-care in type 2 DM patients with diabetic foot ulcers. The research was conducted at the Buleleng Regional General Hospital in 2025. The sample consisted of 63 DM patients with diabetic feet, selected through purposive sampling based on specific inclusion and exclusion criteria. Results: The average age of respondents was 58.92 years. Approximately 60.3% of respondents were female, and 39.7% were male. All respondents had suffered from type 2 DM for more than 5 years. The collected data were statistically analyzed using the Spearman Rank test, yielding a p-value of 0.000 (α = 0.05) and a correlation coefficient (r) of 0.484 There is a significant moderate relationship between self-compassion and self-care in type 2 DM patients experiencing diabetic foot complications. Conclusion: Self-compassion has a positive impact on self-care among patients with diabetic foot. High levels of self-compassion in patients with diabetic foot are directly correlated with an increased capacity for self-care in patients